Processing of Aloe barbadensis Miller - Nagaraju, M.; Ramulla, Suhas; Murthy, N.Y.S. (Asian Journal of Chemistry, 2011)
In the present communication, processing the leaves of both field grown and in vitro cultured Aloe barbadensis Miller plants to produce aloe water and aloe powder are presented. The analysis of aloe powder is also reported.